Bioethics and Media - Zagorac, Ivana (Array, 2011)
This paper will try to stress the importance of media in and for bioethics. Therefore the content is of both practical and theoretical nature. In a first part some data on early media coverage of bioethical issues will be presented. The case of the Dolly the sheep (1997) is marked as the breaking point in a dominant trend of media coverage and its influence is outlined in a second part of the text, followed by a third part concentrated on a phenomenon which could be extracted from those empirical findings, a phenomenon which will be called a bioethical sensibility.